The Correlation between Chitin and Acidic Mammalian Chitinase in Animal Models of Allergic Asthma - Chia-Rui Shen (International Journal of Molecular Sciences, 2015)
Asthma is the result of chronic inflammation of the airways which subsequently results in airway hyper-responsiveness and airflow obstruction. It has been shown that an elicited expression of acidic mammalian chitinase (AMCase) may be involved in the pathogenesis of asthma. Our recent study has demonstrated that the specific suppression of elevated AMCase leads to reduced eosinophilia and Th2-mediated immune responses in an ovalbumin (OVA)-sensitized mouse model of allergic asthma. In the current study, we show that the elicited expression of AMCase in the lung tissues of both ovalbumin- and Der P2-induced allergic asthma mouse models. The effects of allergic mediated molecules on AMCase expression were evaluated by utilizing promoter assay in the lung cells. In fact, the exposure of chitin, a polymerized sugar and the fundamental component of the major allergen mite and several of the inflammatory mediators, showed significant enhancement on AMCase expression. Such obtained results contribute to the basis of developing a promising therapeutic strategy for asthma by silencing AMCase expression.